Training human resources to meet job positions in enterprises in the digital transformation period - Bui Dang Trinh; Le Thi Minh Hoa (Dinasti Publisher, 2025)
In the context of the Fourth Industrial Revolution and rapid digital transformation, the need to align university training with enterprise job requirements has become increasingly urgent. Despite improvements in higher education in Vietnam, a significant gap remains between the competencies of graduates and the evolving expectations of employers. This study aims to develop a validated competency framework to assess the ability of university graduates to meet job positions in enterprises during the digital transformation period. The research integrates both theoretical models and empirical evidence, applying the ASK (Attitudes, Skills, Knowledge) competency framework and the CDIO (Conceive–Design–Implement–Operate) educational approach. Using a mixed-methods design, including expert consultation, in-depth interviews, and quantitative analysis with Cronbach's Alpha, EFA, CFA, and SEM, the study establishes a six-factor model. The model includes: (1) trained knowledge, (2) creative thinking ability, (3) professional skills, (4) communication and teamwork skills, (5) professional autonomy, and (6) ethics and responsibility. The empirical findings confirm that these factors are reliable and valid indicators of job readiness. The study also highlights the importance of university–enterprise collaboration in curriculum design, experiential learning, and resource sharing to enhance graduates' adaptability to digital technologies such as AI, IoT, and Big Data. The research contributes a scientifically grounded tool for measuring competency alignment with labor market demands and offers practical implications for higher education institutions aiming to modernize training programs. Ultimately, the study provides a foundation for universities to reform education in response to the demands of Industry 4.0 and the digital economy, thereby improving employability and sustainable workforce development.